Buku Ajar Speaking For Academic Purposes - Santoso, Dian Rahma; Taufiq, Wahyu (Umsida Press, 2021)
Praise be to our gratitude for the presence of Allah SWT, for His grace and mercy, the Speaking for Academic Purposes Textbook can be completed properly and without significant obstacles. The authors would like to thank: 1. Dr. Akhtim Wahyuni, M.Ag., the Dean of the Faculty of Psychology and Education, who provided direction and motivation to the authors in completing this textbook. 2. Yuli Astutik, M.Pd., the Head of English Education Study Program, who has provided support to compile this textbook. 3. Fellow speaking lecturers in the English Education Study Program who have shared experiences in teaching these courses. Suggestions and critics are highly expected by the authors to create a better Speaking for Academic Purposes textbook and of course in accordance with the mandate of the applicable regulations. Thank you.